2023
DOI: 10.1155/2023/7483783
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Urine and Genital Samples for Detecting Human Papillomavirus (HPV) in Clinical Patients

Abstract: Background. Human papillomavirus (HPV) is the main cause of cervical cancer. The aim of the present study was to investigate HPV DNA detection and genotyping on paired genital and urine samples and to evaluate if urine samples could be used to monitor HPV infection. Methods. Study subjects were recruited from one local hospital in Guangdong of China from September 1, 2011, to June 30, 2012. They were invited to participate if they have taken an HPV genotyping assay for clinical diagnosis of the genital-urinary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The amount of human DNA in urine is also variable between samples or individuals and the optimal volume of the urine to be collected has not been established yet [44][45][46]. The performance of HPV DNA detection in urine is better in women with more severe cervical diseases that may cause more exfoliated cervical cells in urine [47]. Overall, the use of MB as a diagnostic specimen of HPV detection and GTI detection may increase women's participation in cervical cancer screening, as well as GTI screening.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of human DNA in urine is also variable between samples or individuals and the optimal volume of the urine to be collected has not been established yet [44][45][46]. The performance of HPV DNA detection in urine is better in women with more severe cervical diseases that may cause more exfoliated cervical cells in urine [47]. Overall, the use of MB as a diagnostic specimen of HPV detection and GTI detection may increase women's participation in cervical cancer screening, as well as GTI screening.…”
Section: Discussionmentioning
confidence: 99%
“… 25 , 26 , 27 , 28 , 29 , 30 While urine has been found to yield similar results to self‐collected vaginal specimens, some investigations have indicated that urine may be less sensitive than vaginal samples. 31 This discrepancy has been attributed to the lower concentration of HPV DNA in urine compared to cervical samples, necessitating the development of a highly sensitive detection method to ensure ample HPV DNA detection. 25 , 26 , 27 , 28 Additionally, various factors such as storage conditions, DNA extraction and amplification methodology, and transportation have been shown to influence urine test results, leading to significant variability in clinical performance.…”
Section: Discussionmentioning
confidence: 99%